2014
DOI: 10.12693/aphyspola.125.a-57
|View full text |Cite
|
Sign up to set email alerts
|

Optical Spectroscopy Study of the Interaction Between Quercetin and Human Serum Albumin

Abstract: Optical methods are very useful for the study on behavior of molecules in albumin-containing solutions. The interaction between quercetin (QUE) and human serum albumin (HSA) under physiological conditions was investigated by the methods of UV-Vis absorption and uorescence spectroscopy. Fluorescence data show that enhancing of quercetin uorescence in the presence of HSA is the result of formation of the HSA-QUE complex. On the basis of uorescence data, the binding anity constant of quercetin to HSA is determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…However, TGA analysis was failed to calculate the accurate drug-loading rate, since Quercetin was decomposed slowly over a wide temperature range. What’s worse, in vitro drug-release study was also not successful due to the fact that the Quercetin was hard to dissolve in PBS and easy to oxidize [ 325 ]. Cell experiments indicated that the drug-loaded COF successfully killed most of human breast carcinoma MDA-MB-231 cells while the bare COFs showed no cytotoxicity.…”
Section: Cofs For Biomedical Applicationsmentioning
confidence: 99%
“…However, TGA analysis was failed to calculate the accurate drug-loading rate, since Quercetin was decomposed slowly over a wide temperature range. What’s worse, in vitro drug-release study was also not successful due to the fact that the Quercetin was hard to dissolve in PBS and easy to oxidize [ 325 ]. Cell experiments indicated that the drug-loaded COF successfully killed most of human breast carcinoma MDA-MB-231 cells while the bare COFs showed no cytotoxicity.…”
Section: Cofs For Biomedical Applicationsmentioning
confidence: 99%
“…The amount of quercetin entrapped in liposomes was determined through the indirect method based on the measurement of the drug present in the external phase [ 22 ]. After the centrifugation process in the liposomes preparation, the supernatant containing free drug was analyzed for the drug content via double beam UV-VIS spectrophotometer (Shanghai Mapada Instruments UV-6100, China) at 268 nm and 375 nm where the quercetin exhibits two major absorption peaks [ 23 ]. Although the absorbance values at both wavelengths were recorded, data collected at 268 nm was used in all calculations due to high consistency.…”
Section: Methodsmentioning
confidence: 99%
“…Fluorescence spectroscopic studies Investigation of the interactions between quercetin and macromolecules. In particular, it was used in the formation of the dimeric assemblies of quercetin with cyclodextrins [91,[174][175][176][177][178][179][180].…”
Section: Molecular Dynamicsmentioning
confidence: 99%